Exploring outdoor mathematics learning for conceptual understanding through smartphones - Pop, Vuyani Samuel (Rhodes University, Faculty of Education, Department of Secondary and Post School Education)
This study investigated how selected grade 11 mathematics learners used smartphones with the MathCityMap application to learn trigonometry outdoors for conceptual understanding. The aim of this research project was to explore outdoor mathematics learning for conceptual understanding using smartphones. This case study of grade 11 mathematics learners in Lejweleputswa District in the Free State Province, was informed by the Realistic Mathematics Education theory. The study is grounded within an interpretive paradigm and used the explanatory sequential mixed-method design. Forty-two grade 11 mathematics learners participated in the survey and from these 12 were purposively selected to participate in walking the mathematics trails and interviews. The findings revealed that, while the grade 11 mathematics learners acknowledged the significance and value of using smartphones for learning mathematics, they were prohibited from carrying or using smartphones on the school premises, as part of the school code of conduct. The preferred use of smartphones for learning mathematics was understandable, as the survey was conducted at a time when the COVID-19 pandemic and associated restrictions were still in place. The survey unearthed that among applications for learning mathematics, the MathCityMap application was not known by the learners who participated in the survey. Mathematics trails observations indicated that outdoor tasks were a source of mathematical concepts or formal mathematical knowledge, and enabled learners to reinvent mathematical ideas and concepts with adult guidance. Learners were able to make use of appropriate mathematical models and connections. The mathematics trails ignited robust discussions among learners, and prompted learners to draw from prior knowledge, and recognise and identify suitable mathematical models and shapes from the real-world objects. Learners were able to use multiple representations, make necessary mathematical links, and use their prior knowledge to enhance their trigonometry conceptual understanding. This study concluded that using smartphones with the MathCityMap application could enhance conceptual understanding of trigonometry. The implications for teachers are that learners should be exposed to outdoor mathematics learning using smartphones with the MathCityMap application to improve their conceptual understanding. It is hoped that the results of this study can be used by various stakeholders, who include, inter alia, mathematics subject advisors and teacher training institutions, to enhance learners' conceptual understanding of mathematics.
Keywords: Mathematics-- Study and teaching (Secondary) -- South Africa Lejweleputswa District Municipality; Educational technology; Mobile communication systems in education; Math walk; Concept learning